Multipotential differentiation of human urine‐derived stem cells: Potential for therapeutic applications in urology1. (4th October 2013) - Bharadwaj, Shantaram; Liu, Guihua; Shi, Yingai; Wu, Rongpei; Yang, Bin; He, Tongchuan; Fan, Yuxin; Lu, Xinyan; Zhou, Xiaobo; Liu, Hong; Atala, Anthony; Rohozinski, Jan; et al.
Abstract : We sought to biologically characterize and identify a subpopulation of urine‐derived stem cells (USCs) with the capacity for multipotent differentiation. We demonstrated that single USCs can expand to a large population with 60–70 population doublings. Nine of 15 individual USC clones expressed detectable levels of telomerase and have long telomeres. These cells expressed pericyte and mesenchymal stem cell markers. Upon induction with appropriate media in vitro, USCs differentiated into bladder‐associated cell types, including functional urothelial and smooth muscle cell lineages. When the differentiated USCs were seeded onto a scaffold and subcutaneously implanted into nude mice, multilayered tissue‐like structures formed consisting of urothelium and smooth muscle. Additionally, USCs were able to differentiate into endothelial, osteogenic, chondrogenic, adipogenic, skeletal myogenic, and neurogenic lineages but did not form teratomas during the 1‐month study despite telomerase activity. USCs may be useful in cell‐based therapies and tissue engineering applications, including urogenital reconstruction. STEM Cells 2013;